Albert B. Lord, Pieśniarz i jego opowieść. Przeł. Paweł Majewski. Red. naukowy Grzegorz Godlewski. Warszawa 2010, ss. 528. - Matkowska, Agnieszka (Porównania, 2012)
Albert B. Lord, Pieśniarz i jego opowieść. Przeł. Paweł Majewski. Red. naukowy Grzegorz Godlewski. Warszawa 2010, ss. 528.